2022
DOI: 10.35784/pe.2022.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Assessment of Tax Measures in the European Countries Against the Effects of COVID-19

Abstract: Ongoing global COVID-19 pandemic is not only health crisis but the economic challenge. The future of society depends on how successfully the authorities find a balance between imposition of stringent restrictions and economic development. Tax policies play a role in reducing losses caused by the COVID-19 lockdowns. All countries are taking tax measures to mitigate the impact of the effects of COVID-19 pandemic on society. While the COVID-19 pandemic has not yet been defeated, it is too early to draw conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the first phase of this study, primary data was collected between 2020 and 2021 because it is a cross-sectional study, the process had done by emails and phone due to COVID-19 restrictions (Bilenko et al, 2022), and the literature was updated and written by reviewing the articles related to the topic and the chosen variables.…”
Section: Methodsmentioning
confidence: 99%
“…In the first phase of this study, primary data was collected between 2020 and 2021 because it is a cross-sectional study, the process had done by emails and phone due to COVID-19 restrictions (Bilenko et al, 2022), and the literature was updated and written by reviewing the articles related to the topic and the chosen variables.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative assessment (Bilenko et al, 2022) of the impact of innovative development in the energy sector on the development of the national economy was conducted using factor analysis using a factor analysis model:…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, scientists have moved from theoretical to practical research, as enough historical data has been accumulated. For the period from 2014 to 2018, 146 Proof-of-Work-based cryptocurrencies were examined (Bilenko et al, 2022). It was found that about 60% of those cryptocurrencies were eventually in default (Grobys & Sapkota, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%